History, Typology, and Implementation of Islamic Law in Indonesia: Combination of Sharia and Fiqh or the Result of Historical Evolution? - Afridawati, Afridawati (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2021)
This paper highlights the history, typology, and implementation of Islamic law in Indonesia as well as proves that the law is a translation of both sharia and fiqh, rather than a historical evolution, as claimed by Ignaz Goldziher (1850 - 1921 AD) and some of his Muslim followers; nor does the law separate elements of ritual, muamalah, and politics as argued by Christian Snouck Hurgronje (1857–1936 AD), a stance that has deformalized Islamic law in Indonesia considering it an inferior legal institution. Focusing on Islamic civil law which is extracted from relevant literature sources, this paper shows that, to some extent, the influence of orientalists’ views is manifested, for example, in the books of Interfaith Jurisprudence and the Counter Legal Draft of Islamic Law Compilation (CLD - KHI) which have ample of